Pembuatan Training Kit Pneumatik untuk SMKN I Ngawen Kabupaten Gunungkidul - Budi Basuki (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
Community Service Activities (PKM) of Department of Mechanical Engineering (DTM), Vocational College, Universitas Gadjah Mada 2015 is entitled the development of pneumatic training kit for SMK N I Ngawen, Gunungkidul Regency. The school located in Jono Hamlet, Tancep Village, Ngawen District, Gunungkidul Regency, has a land area of 15,300 m2. There are four competency expertise held in this school, namely: Light Vehicle Technique, Heavy Equipment, Computer and Network Engineering, and Batik Clothing. SMK N I Ngawen and Vocational College (in this case Mechanical Engineering Department as a PKM team directly involved) have established cooperation in the field of heavy equipment education. SMK N I Ngawen actively has planning and effort of developing PLC control technique as a tool of practice to support the competence of machine expertise. After conducting surveys and coordination with the Principal and its staff, the PLC's control engineering development activities are planned to include scheduling, coordination of PLC training for educator staff, procurement of PLC units, the creation of pneumatic training kit simulators and completeness, the administration of activities and technical details . The procurement of PLC control techniques and pneumatic training kits was successfully carried out for 6 (six) months smoothly from April to October 2015. This activity was conducted on campus of DTM SV - UGM and in SMK N I Ngawen. Implementation of this training kit was conducted by PKM team and education staffs of SMK N I Ngawen Gunungkidul. The preparation of pneumatic training kits begins with the purchase and preparation of training components to the preparation of layouts and testing of training kits. The delivery of pneumatic training kits was done after the teaching staffs of SMK N I Ngawen Gunungkidul attended training kit training.